Times Video: o papel estratégico da produção audiovisual no The New York Times | Video Time: O the Strategic Role of Audiovisual Production Without The New York Times - Dantas-de-Oliveira-Penteado, Julia; Porto-Renó, Denis (Razón y Palabra, 2016)
Vivemos em um momento disruptivo no jornalismo. Os jornais que pretendem sobreviver devem transformar os processos de produção jornalística. Entre as mudanças necessárias, está a produção de conteúdo multimídia, foco do presente artigo. Para ilustrar tais mudanças, foi realizado um estudo de caso do jornal The New York Times no campo audiovisual. The journalism industry is facing a disruptive moment. The news companies that intend to survive must transform the whole process of making journalism. Among other changes, there is a need of producing multimedia content, which is the focus of the present paper. To illustrate these changes, it was studied the case of The New York Times newspaper company in the video field.